A Contribution in Evaluation of Seismic Response Modification Factor for Structural Base Isolated Systems - طيار, طوني; بسام حويجة; نزيه منصور (Latakia University Journal -Engineering Sciences Series, 2023)
In recent years, structural engineering has witnessed many modern technologies that helped to improve the performance of buildings in the face of natural loads such as winds and earthquakes. This large spread in the use of this technology forced us, as structural engineers, to know the methods of designing this type of buildings and to expand in their analysis methods. And in considering the seismic response modification factor or the so-called inelastic behavior coefficient (R factor) as one of the important parameters in the structural design process of buildings exposed to seismic risk, the aim of this research was to study the values ​​of the RI factor for the isolated buildings and compare them with what is stipulated in the international codes that related with this kind of structural systems , which we found to show a kind of reservation towards the values ​​of the RI factor, which in turn is reflected in the economical design. In order to reach the goal of the research, we used static nonlinear pushover analysis on a group of building models and studied the effect of changing some parameters such as the number of floors, damping ratios, and stiffness on the behavior of these models, in addition to conducting a dynamic nonlinear analysis of the models based on the time record of the Centro earthquake, and Reaching values ​​for the RI factor, which were in turn different from what was stated in international codes such as ASCE 7-16, IBC2000.